Cushing’s disease with twin pregnancy and diabetes mellitus: a case report and literature review - Hideyasu Asai; Ikuo Yamamori; Shigeru Hagimoto; Kyoichi Okumura; Koki Sakakibara (Endocrine Journal)
A 38-year-old Japanese woman with a history of abnormal thyroid function of non-autoimmune origin, pituitary endocrine tumor, and untreated diabetes mellitus was referred to our outpatient clinic when she became pregnant with twins. Physical findings consistent with Cushing’s syndrome (CS) were absent at the time of presentation. Although baseline plasma adrenocorticotropic hormone, serum cortisol, and 24-hour urinary free cortisol excretion levels were above the upper limits of normal non-pregnant reference ranges, we could not exclude a physiological increase associated with pregnancy. No medical or surgical intervention for hypercortisolism was performed during pregnancy. Spontaneous vaginal delivery resulted in the normal delivery of live twins. A diagnosis of Cushing’s disease (CD) was established when papery skin developed postpartum. Transsphenoidal surgery was performed and the hypercortisolism partially resolved post-operatively. The patient’s abnormal thyroid function also resolved. Pregnancy in women with endogenous CS is rare, with less than 300 cases reported. Most reported cases of CS during pregnancy are of adrenal origin. Only two cases of twin pregnancies with CD have been reported. Therefore, we reported the third case of CD in a twin pregnancy and reviewed the diagnostic and therapeutic challenges associated with CD during pregnancy.